Integrated Analysis of Prognostic Genes Associated With Ischemia–Reperfusion Injury in Renal Transplantation - Zhang, Di; Wang, Yicun; Zeng, Song; Zhang, Min; Zhang, Xin; Wang, Yuxuan; Zhang, Zijian; Wang, Xi; Hu, Xiaopeng (Frontiers in Immunology, 2021)
Background: Ischemia-reperfusion injury (IRI) remains an inevitable and major challenge in renal transplantation. The current study aims to obtain deep insights into underlying mechanisms and seek prognostic genes as potential therapeutic targets for renal IRI (RIRI). Methods: After systematically screened the Gene Expression Omnibus (GEO) database, we collected gene expression profiles of over 1000 specimens from 11 independent cohorts. Differentially expressed genes (DEGs) were identified by comparing allograft kidney biopsies taken before and after reperfusion in the discovery cohort and further validated in another two independent transplant cohorts. Then, graft survival analysis and immune cell analysis of DEGs were performed in another independent renal transplant cohort with long-term follow-ups to further screen out prognostic genes. Cell type and time course analyses were performed for investigating the expression pattern of prognostic genes in more dimensions utilizing mice RIRI model. Finally, two novel genes firstly identified in RIRI were verified in mice model, and comprehensively analyzed to investigate potential mechanisms. Results: Twenty DEGs upregulated in the process of RIRI throughout different donor types (living donors, cardiac and brain death donors) were successfully identified and validated. Among them, upregulation of ten genes was associated with poor long-term allograft outcomes and exhibited strong correlations with prognostic immune cells, like macrophages. Furthermore, certain genes were found to be only differentially expressed in specific cell types and remained high expression levels even months after RIRI in mice model, which processed the potential to serve as therapeutic targets. Importantly, two newly identified genes in RIRI, Btg2 and Rhob, were successfully confirmed in mice model and found to have strong connections with NF-κB signaling. Conclusions: We successfully identified and validated ten IRI-associated prognostic genes in renal transplantation across different donor types, and two novel genes with crucial roles in RIRI were recognized for the first time. Our findings offered promising potential therapeutic targets for RIRI in renal transplantation.